Impact of Kashmir floods on the libraries. Issue 2 (3rd April 2017) - Wani, Zahid Ashraf; Ganaie, Ansaar Hussain
Abstract : Purpose: This paper aims to highlight the damage suffered by the prominent libraries of Kashmir during September 2014 floods. The work provide an insight about the response and recovery measures being taken during and after the floods respectively in ten prominent libraries of Jammu & Kashmir [six Academic libraries (S.P. College Library, Women's College Library, Govt. Degree College Library – Bemina, Amar Singh College Library, Gandhi Memorial College Library and College of Education Library); three Special libraries (J&K Academy of Art, Culture & Languages Library – Srinagar, Govt. Medical College Library – Srinagar and J&K High Court Library) and one Public library (Sri Pratap Singh library)]. Design/methodology/approach: A variety of data collection tools and techniques such as interview, questionnaire, observation, etc., were used to collect the data. The collected data have been tabulated and analyzed to derive meaningful conclusions and findings as per the set objectives of the study. Findings: The results reveal that although libraries in Kashmir are prone to disasters like floods; yet, none of the library seems to be prepared to bear or cope such a disaster. The findings provide a gloomy picture of libraries when it comes to the measures being taken by these libraries during and after the floods to protect their resources. The paper highlights the inefficiency and incapability of libraries (in terms of disaster management) by finding that most of the libraries are without a disaster response and recovery plan as well as a disaster response and recovery team. The study recommends that some tangible measures if taken can save precious resources hosted in libraries. Practical implications: The current study can help the stakeholders to chalk out scientific and systematic policy and plans for library and information centers that can be executed with minimum of fuss and anarchy. Originality/value: The study offers working knowledge to library professional on ground for effective management of assets and resources in pre- and post-disaster scenario.